2010
DOI: 10.5604/20831862.913078
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin converting enzyme gene i/d polymorphism in ellite polish and lithuanian judo players

Abstract: T H E A N G I O T E N S I N C O N V E R T I N G ENZYME GENE I/D POLYMORPHISM IN ELLITE POLISH AND LITHUANIAN JUDO PLAYERSp=0.019). Our investigation have proved the ACE I/D allele could be one of the factors influencing the elite endurance exercise performance. The research suggests that those most predisposed to judo are individuals with the allele distribution in the ACE gene that is most significant with regard to the duration of a fight, and not with regard to the character of the performed moves, as could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
(28 reference statements)
4
10
3
Order By: Relevance
“…All DNA samples were normalized to 1 ng of DNA per 1 microliter. Regions of ACNT3 and ACE genes containing studied polymorphisms (rs1815739 and rs4646994, respectively) were amplified by polymerase chain reaction (PCR), using 1 nanogram of DNA sample, previously published flanking primers (Mills et al 2001;Cieszczyk et al 2010) at a final concentration of 0.3 µM each, and MeltDoctor™ HRM Master Mix (Thermo Fisher Scientific) in a total volume of 20 microliters. PCR amplification and melting of the PCR products were performed in ViiA 7 machine (Applied Biosystems), running QuantStudio Real Time PCR software, ver.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…All DNA samples were normalized to 1 ng of DNA per 1 microliter. Regions of ACNT3 and ACE genes containing studied polymorphisms (rs1815739 and rs4646994, respectively) were amplified by polymerase chain reaction (PCR), using 1 nanogram of DNA sample, previously published flanking primers (Mills et al 2001;Cieszczyk et al 2010) at a final concentration of 0.3 µM each, and MeltDoctor™ HRM Master Mix (Thermo Fisher Scientific) in a total volume of 20 microliters. PCR amplification and melting of the PCR products were performed in ViiA 7 machine (Applied Biosystems), running QuantStudio Real Time PCR software, ver.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…Melting profiles were assessed using high Resolution Melt (HRM) Software Module for ViiA™ 7 System (Applied Biosystems™), able to identify gene variants based on the differences in the shape of the melt curves and the differences in the values of melting temperature of amplicons. Accuracy of the HRM genotyping was checked by comparing results to those obtained for a subset of samples genotyped by conventional methods (gel electrophoresis for I/D polymorphism in ACE gene, according to the previously published protocol (Cieszczyk et al 2010), and restriction fragment length polymorphism (RFLP) analysis for R577X mutation in ACTN3 gene (Mills et al 2001). Perfect concordance between genotyping results obtained using different methods proved 100% analytical specificity of this, in house developed, HRM method for accurate genotyping of these polymorphisms.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…In fact, recent research showed higher frequency of the I allele and II genotype in the angiotensin-converting enzyme (ACE) gene (which theoretically would favor endurance performance) in elite Polish and Lithuanian judokas, suggesting that genetic predisposition for longer fighting is at least as important (if not more so) than genetic predispositions to speed or power. 9 Although the contribution of genetics to sportsrelated phenotype traits is undeniable with some genotypes, of which ACTN3 R577X is currently the leading candidate, partly distinguishing individuals predisposed to either endurance or power sports, few athletic events can be categorized as purely power or endurance based; as such, sports performance is usually polygenic and not simply reducible to single candidate gene variants. There are indeed numerous other contributors to the complex trait of being an athletic champion that are likely not reducible to defined genetic polymorphisms, included complex gene-gene and gene-environment interaction and interactions between genetic variants that might not influence sports performance individually.…”
mentioning
confidence: 99%
“…For the ACE, although two studies observed different genotype and allele distributions between athletes and the control groups, one (Cieszczyk et al, 2010) reported a low occurrence of DD genotype and a significant excess of the I allele in judo athletes, while the other (Kikuchi et al, 2012) observed a higher frequency of the DD genotype and an association between the D allele and elite wrestler status. Because judo and wrestling are grappling combat sports with similar metabolic demands (Franchini et al, 2011;Yoon, 2002), the difference observed between these two studies can attributed to the competitive level of the athletes (national level judo athletes and international level wrestlers) or by the training system used in different countries.…”
Section: Ckmmentioning
confidence: 99%
“…Concerning allele frequency (Figure 2), from the studies analysed the following results were observed when combat sports athletes and controls were compared: (1) ACTN3 -no difference for the three studies that investigated it (Kikuchi et al, 2012;Kikuchi et al, 2013;Rodríguez-Romo et al, 2013); (2) ACE -two studies reported difference between the athletes and the control groups (Cieszczyk et al, 2010;Kikuchi et al, 2012); (3) PPARα -one observed higher frequency (Cieszczyk et al, 2011), but the other did not (Ahmetov et al, 2006); (4) CKM -one found a higher frequency (Fedotovskaya et al, 2013).…”
Section: Ckmmentioning
confidence: 99%